2021
DOI: 10.3389/fmolb.2021.679949
|View full text |Cite
|
Sign up to set email alerts
|

Varied Contribution of Phospholipid Shedding From Membrane to Daptomycin Tolerance in Staphylococcus aureus

Abstract: It has been suggested that daptomycin can be inactivated by lipids released by Staphylococcus aureus and that this effect is antagonized by phenol soluble modulins (PSMs), which bind to the shed lipids. PSM production is regulated by the Agr system, and others have shown that loss of the Agr function enhances S. aureus survival in the presence of daptomycin. Here we assessed the impact of Agr function on daptomycin activity and lipid metabolism under various conditions. Daptomycin activity was evaluated agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For instance, S. aureus inactivates daptomycin by releasing membrane phospholipids into the extracellular space, thereby sequestering daptomycin and preventing it from inserting into the bacterial membrane ( Pader et al, 2016 ). Strains with different genetic backgrounds may exhibit different contributions of phospholipid shedding and hence have different tolerance levels to daptomycin ( Shen et al, 2021 ). Indeed, in our previous study, we found that reduced daptomycin tolerance in MRSA was associated with a reduced lipid metabolic process ( Sulaiman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, S. aureus inactivates daptomycin by releasing membrane phospholipids into the extracellular space, thereby sequestering daptomycin and preventing it from inserting into the bacterial membrane ( Pader et al, 2016 ). Strains with different genetic backgrounds may exhibit different contributions of phospholipid shedding and hence have different tolerance levels to daptomycin ( Shen et al, 2021 ). Indeed, in our previous study, we found that reduced daptomycin tolerance in MRSA was associated with a reduced lipid metabolic process ( Sulaiman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, daptomycin-induced phospholipid release does not occur in all strains of S. aureus , which may provide a route to a greater mechanistic understanding of this phenomenon [205, 206].…”
Section: Inactivation Of Polymyxins and Daptomycin Via Membrane Decoysmentioning
confidence: 99%
“…This process appears require phospholipid biosynthesis, since the presence the fatty acid synthesis (FASII) inhibitor AFN-1252 blocks daptomycin-induced phospholipid release, suggesting it is not simply a consequence of daptomycin-mediated membrane damage [205]. Furthermore, daptomycin-induced phospholipid release does not occur in all strains of S. aureus, which may provide a route to a greater mechanistic understanding of this phenomenon [205,206].…”
Section: Inactivation Of Polymyxins and Daptomycin Via Membrane Decoysmentioning
confidence: 99%
“…Nonetheless, studies such as these lay the foundation for future work, with biomarker discovery not feasible without the availability of comprehensive profiles and initial exploratory analysis. Studies by Hines et al, however, circumvented these issues by employing a hydrophilic interaction LC-ion mobility-MS (HILIC-IM-MS) method to separate lipids based on both head group polarity and gas phase structure, facilitating more powerful discrimination [93] , [94] , [95] . Results validated those of Rashid et al, and revealed alterations in the lipid profiles of daptomycin-resistant MRSA and Corynebacterium striatum [92] , [93] .…”
Section: Lipidomicsmentioning
confidence: 99%